Table 2_Identification of lysozyme in Venetin-1 nanoparticle from the coelomic fluid of the earthworm Dendrobaena veneta.csv - Marta J. Fiołka (6444206) (2025)
Background In the present study, lysozyme was analyzed in the nanoparticle Venetin-1 obtained from the coelomic fluid (CF) of the earthworm Dendrobaena veneta. Venetin-1 is a protein-polysaccharide complex and has proven anti-cancer (non-small lung cancer, colon cancer, cervical cancer), antifungal and immunostimulating properties. Methods The studies were conducted using methods such as electrophoretic separation, immunodetection, and ELISA determination of lysozyme concentration. Spectroscopic methods such as FTIR and Raman spectroscopy were also employed. Proteomic analyses, SageELF separation, and zeta potential determination were also performed. Cryo-EM was used to determine the molecular structure of Venetin-1. Results The lysozyme-type activity in this compound was significantly higher than in the crude CF. The analysis showed the highest concentration of lysozyme recognized by antibodies directed against human lysozyme is in the fraction containing compounds with a mass above 100 kDa and in the preparation obtained using a cut-off point of 6–8 kDa. Raman analysis showed a significant similarity of the protein part of Venetin-1 and EWL. FTIR analyses confirmed that the preparation obtained under these conditions showed high similarity to egg white lysozyme (EWL). Cryo-EM studies revealed the structure of the tested nanoparticle containing both lysozyme and lysenin fragments. Immunoblotting using antibodies directed against human lysozyme revealed proteins of mass 11, 33, 44, 88 and 132 kDa recognized in Venetin-1. Proteomic analyses confirmed the presence of these proteins and similarity to human lysozyme. Conclusion These observations suggest the presence of polymeric forms of lysozyme in the tested complex, and zeta potential analysis revealed properties of the nanoparticle that predispose it to use in medicine.